Artificial microRNA-mediated resistance against Oman strain of tomato yellow leaf curl virus - Al-Roshdi, Maha R.; Ammara, Ume; Khan, Jamal; Al-Sadi, Abdullah M.; Shahid, Muhammad Shafiq (Frontiers in Plant Science, 2023)
Tomato yellow leaf curl virus (TYLCV) is a global spreading begomovirus that is exerting a major restraint on global tomato production. In this transgenic approach, an RNA interference (RNAi)-based construct consisting of sequences of an artificial microRNA (amiRNA), a group of small RNA molecules necessary for plant cell development, signal transduction, and stimulus to biotic and abiotic disease was engineered targeting the AC1/Rep gene of the Oman strain of TYLCV-OM. The Rep-amiRNA constructs presented an effective approach in regulating the expression of the Rep gene against TYLCV as a silencing target to create transgenic Solanum lycopersicum L. plant tolerance against TYLCV infection. Molecular diagnosis by PCR followed by a Southern hybridization analysis were performed to confirm the effectiveness of agrobacterium-mediated transformation in T0/T1-transformed plants. A substantial decrease in virus replication was observed when T1 transgenic tomato plants were challenged with the TYLCV-OM infectious construct. Although natural resistance options against TYLCV infection are not accessible, the current study proposes that genetically transformed tomato plants expressing amiRNA could be a potential approach for engineering tolerance in plants against TYLCV infection and conceivably for the inhibition of viral diseases against different strains of whitefly-transmitted begomoviruses in Oman.